Factors associated with purchasing pesticide from shops for intentional self-poisoning in Sri Lanka - Weerasinghe, M; Konradsen, F; Eddleston, M; Pearson, M; Jayamanne, S; Knipe, D; Hawton, K; Gunnell, D; Agampodi, S (Wiley, 2020)
Objective In South Asia, up to one in five individuals who ingest pesticides for self‐poisoning and survive purchased them from a shop immediately prior to the event. Thus far, no research has taken place to determine whether interventions implemented through the pesticide sellers might be acceptable or effective, despite the hundreds of thousands of such risk purchases each year. We aimed to investigate factors associated with purchasing pesticides for self‐poisoning in Sri Lanka.